Measuring People's Minds and Lives - Cahill, Mildred; Martland, Sandra (Canadian Journal of Counselling and Psychotherapy, 2007)
The increasing pluralism of Canadian society has opened up new avenues for research into levels of cultural identity, components of value-systems, interactions between people of different values, and effects of these on career development. The political, economic, and social shifts that are occurring today provide an opportunity to look at the contextual dimensions of career development. In this article, the authors caution career development investigators and/or practitioners to also attend to the needs of the less visible, minority cultures, for eg., those based on geographic location, throughout the country.